AWARENESS AND PRACTICE OF PHYSICAL ACTIVITY AMONG MALE MEDICAL UNDERGRADUATES AT MAJMAAH UNIVERSITY, SAUDI ARABIA: Physical Activity Among Male Medical Undergraduates - Farhan, Muhammad Asad; Kazmi, Syed Yousaf; Irfan, Abdul; Sami, Waqas; Faraz, Ali; Ali, Muhammad Imram (Pakistan Armed Forces Medical Journal, 2021)
Objective: To probe the level of awareness and practice of the WHO recommendation for physical activity among male medical undergraduates at Majmaah University, Saudi Arabia. Study Design: Cross-sectional analytical study. Place and Duration of Study: College of Medicine, Majmaah University, Kingdom of Saudia Arabia from Oct to Dec 2018. Methodology: The study was conducted amongst 150 undergraduate medical students using a self-validated questionnaire. Results: A total of 53 (35.33%) participants were found to be physically inactive while only 18 (12%) participants were adherent to WHO recommendations of physical activity for health benefits. Only 31 (20.66%) participants were correctly aware of the WHO guidelines for physical activity with health benefits. Football (n=47) and table tennis (n=20) were the sports played by the majority i.e., in 67 (44.66%) participants. The physically active participants encouraged peers for physical activity and preferred social media as a mean of spreading awareness about physical activity. Conclusion: The awareness and the level of adherence of our male medical undergraduate students of physical activity according to the WHO’s guidelines are at par with the results of the national studies but much lower than the developed countries like the USA.